Generalized stochastic profiling of transcriptional regulatory heterogeneities in tissues, tumors, and cultured cells - Wang, Lixin (2013)
Single-cell variations in gene and protein expression are important during development and disease. Cell-to-cell heterogeneities can be directly inspected one cell at a time, but global methods are usually not sensitive enough to work with such a small amount of starting material. Here, we provide a detailed protocol for stochastic profiling, a method that infers single-cell regulatory heterogeneities by repeatedly sampling small collections of cells at random. Repeated stochastic sampling is performed by laser capture microdissection or limiting dilution, followed by careful exponential cDNA amplification, hybridization to microarrays, and statistical analysis. Stochastic profiling surveys the transcriptome for programs that are heterogeneously regulated among cellular subpopulations in their native tissue context. The protocol is readily optimized for specific biological applications and takes about one week to complete.